A Novel SDR-Based P-Band PRN Radar With Real Time Range Compression and Coherent Integration - Edwar Edwar; Yasir M. O. Abbas; Shah Zahid Khan; Abdul-Halim Jallad; Adriano Camps (IEEE Access, 2025)
Active microwave remote sensing at P-band offers the potential to map vegetation biomass and subsurface soil moisture. This paper presents the development of a novel Software-Defined Radio (SDR)-based Pseudo-Random Noise (PRN) radar operating at P-band. Utilizing GNU Radio, it is the first one of its kind performing real-time range compression and coherent integration, achieving a signal-to-noise ratio (SNR) of up to 64.4 dB. Operating at a low transmit power of 10 dBm, experimental results validate the system’s performance, demonstrating its potential for remote sensing applications.